Implementasi Media Permainan Ular Tangga dalam Pembelajaran Kosakata Bahasa Arab di Pondok Pesantren Addin Bahrul Ulum Tambakberas Jombang - Chaecilia Dyah Nurlaili; Aufia Aisa (Lembaga Yasin AlSys, 2025)
The limited number of studies on the implementation of innovative non-electronic learning media for Arabic vocabulary instruction in pesantren settings forms the background of this research, given the need for alternative approaches in institutions with limited access to technology. This study aims to analyze the implementation process of the snakes and ladders game as a learning medium and to explore students' perceptions of its use in Arabic vocabulary learning. A qualitative case study design was employed, involving three participants (two female students and one male student) selected through purposive sampling. Data were collected through interviews, observation, and documentation, and analyzed using thematic analysis. The findings reveal positive responses from students regarding the use of the snakes and ladders game, which was perceived as helpful for vocabulary retention, creating an enjoyable learning atmosphere, and fostering social interaction. These results support cooperative learning theory and demonstrate that practical, contextually relevant physical media can enhance motivation and learning outcomes in Arabic instruction within the pesantren environment. The implications of this study include contributions to the literature on gamification in non-digital contexts, as well as practical recommendations for pesantren administrators to provide supportive learning tools and optimize instructional schedules. This research also opens opportunities for further studies with broader samples and the use of mixed methods.